2003
DOI: 10.1016/s1044-0305(03)00451-3
|View full text |Cite
|
Sign up to set email alerts
|

Efficient determination and evaluation of model cyclodextrin complex binding constants by electrospray mass spectrometry

Abstract: Electrospray ionization mass spectrometry (ESI-MS) is now routinely used for the detection of cyclodextrin noncovalent complexes, complementing previously established methods. Hostguest complexes formed in solution are also stable for characterization by ESI in the gas phase. This paper reports the first investigations to characterize the stability of three inclusion complexes between ␤-cyclodextrin (␤-CD) and three model "guest" molecules, by determining the cyclodextrin compound complex stability constant (K… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
42
0
5

Year Published

2004
2004
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(47 citation statements)
references
References 47 publications
(43 reference statements)
0
42
0
5
Order By: Relevance
“…Prilikom stvaranja kompleksa sa β-CD manje polarni deo molekule "gosta" se uvlači u šupljinu, dok su polarnije grupe u kontaktu sa polarnim rastvaračem (8). Tako, fenil grupe molekule "gosta" kao hidrofobne lako se uklapaju u šupljinu β-CD, a amino, alkoholne, fenolne i karbonilne grupe omogućavaju interakcije sa hidrofilnim grupama na spoljašnjoj površini β-CD formiranjem vodoničnih veza, omogućavajući na taj način dodatnu stabilizaciju nagrađenog kompleksa (9). Uklapanje molekula u šupljinu β-CD, odnosno komplementarnost između njihovih veličina, određuje stabilnost kompleksa i selektivnost procesa kompleksiranja (10,11).…”
Section: Uvodunclassified
See 1 more Smart Citation
“…Prilikom stvaranja kompleksa sa β-CD manje polarni deo molekule "gosta" se uvlači u šupljinu, dok su polarnije grupe u kontaktu sa polarnim rastvaračem (8). Tako, fenil grupe molekule "gosta" kao hidrofobne lako se uklapaju u šupljinu β-CD, a amino, alkoholne, fenolne i karbonilne grupe omogućavaju interakcije sa hidrofilnim grupama na spoljašnjoj površini β-CD formiranjem vodoničnih veza, omogućavajući na taj način dodatnu stabilizaciju nagrađenog kompleksa (9). Uklapanje molekula u šupljinu β-CD, odnosno komplementarnost između njihovih veličina, određuje stabilnost kompleksa i selektivnost procesa kompleksiranja (10,11).…”
Section: Uvodunclassified
“…Uklapanje molekula u šupljinu β-CD, odnosno komplementarnost između njihovih veličina, određuje stabilnost kompleksa i selektivnost procesa kompleksiranja (10,11). β-CD i molekul "gost" mogu da formiraju komplekse u različitim odnosima (9).…”
Section: Uvodunclassified
“…After 24 h, the reaction mixture was filtered. The filtrate was extracted with EtOAc (50 mlϫ3), washed with brine and dried over MgSO 4 . After removal of the solvent under reduced pressure, the residue was purified by column chromatography on silica gel with EtOAc : CHCl 3 (1 : 9) as an eluent to give 1.6 g, 93% as a colorless solid.…”
Section: 4-bis(methoxycarbonylmethoxy)diphenylmethane (4)mentioning
confidence: 99%
“…Recently, it reported that mass spectrometry can be used to detect noncovalent association complexes. [1][2][3][4] We reported that FAB-MS is useful method as well as 1 H-NMR method not only for confirmation of TGDMAP (1) and biological relevant phosphates such as nucleotide complex geometry but also for determination of stability constant (K s ) values of the complexes because the K s value calculated by FAB-MS (100 M Ϫ1 for UMP) was most similar to the K s value calculated by 1 H-NMR spectrometry (110 M Ϫ1 for UMP). …”
mentioning
confidence: 99%
“…The cited review articles indicate a wealth of applications in the areas of protein (enzyme)-ligand and oligonucleotide (RNA, DNA)-ligand interaction systems. With respect to small molecule [37][38][39][40][41][42][43][44] and chiral recognition systems [25,26,28,[45][46][47][48], far fewer quantitative solutionphase affinity studies have been reported utilizing ESI-MS. The majority of work relating the application of mass spectrometry to studying enantioselective interactions has centered on gas-phase tandem mass spectrometric (e.g., by ion/molecule reactions and the kinetic method) or desorption mass spectrometric (e.g., by fast atom bombardment) experiments [49 -58].…”
mentioning
confidence: 99%